Bioethical approximation to preimplantation genetic diagnosis for third party therapeutic purposes - Carrasco Salgado, Nataly Cristina (2019)
This article introduces a bioethical approximation to preimplantation genetic diagnosis (PGD) for third party therapeutic purposes, a procedure in which the human person is subject to several considerations that affect their vital development from their beginnings. This reflection considers anthropological, bioethical and legal aspects.